Genomic disorders: mechanisms for copy number variation and clinical implementation of high-resolution genome analysis - Lupski, James (Henry Stewart Talks, 2009)
Rearrangements of the human genome as a significant source for genetic variation, Genomic disorders, Inherited and sporadic traits, Rearrangements associated with genomic disorders can be recurrent, with breakpoint clusters resulting in a common sized deletion/duplication, or nonrecurrent and of different sizes, Nonallelic homologous recombination (NAHR), Nonhomologous end-joining (NHEJ), Low-copy repeats (LCRs), Fork Stalling and Template Switching (FoSTeS), Rearrangements as an evolutionary function, Gene dosage, position effects, unmasking of coding region mutations (cSNPs) and other functional SNPs, De novo genomic rearrangements have been shown to cause both chromosomal and Mendelian disease, as well as sporadic traits, Understanding of the extent to which genomic rearrangements, gene CNV, and/or gene dosage alterations are responsible for common and complex traits remains rudimentary